KARAKTERISTIK STATUS GIZI PADA ANAK USIA SEKOLAH DASAR DI SD NEGERI 018 LANGGINI - Sa'adah, Farra Ana (Universitas Pahlawan Tuanku Tambusai, 2024)
Nutritional status represents what a person consumes over a long period of time. This is because school children are among the groups vulnerable to nutritional problems. Not paying attention to the food they consume will affect their nutritional status. Based on the 2018 Riskesdas data, the nutritional status of children aged 5-12 years in Riau province shows a prevalence of thinness at 9.9%, consisting of 2.7% in the very thin category and 7.2% in the thin category. The prevalence of overweight is at 17.5%, with 9.1% classified as overweight and 8.4% classified as obese. The aim of the research is to determine the characteristics of the nutritional status of school-age children at SDN 018 Langgini. This is a quantitative study with a descriptive design. The research was conducted on November 4, 2023, with a sample size of 51 elementary school children using the Total Sampling technique. Data collection was conducted using questionnaires. The data analysis used is univariate analysis. The univariate analysis results showed that 15 respondents (29%) were 11 years old, 26 respondents (51%) were male, 29 respondents (57%) had good nutritional status, 50 respondents (98%) had good eating habits, and 39 respondents (76%) had good physical activity. The conclusion is that 50 respondents (98%) had good eating habits, 39 respondents (76%) had good physical activity, and 29 respondents (57%) had good nutritional status. Schools can collaborate with community health centers or local health institutions to conduct regular nutritional status checks for all students. This can help in early detection of nutritional problems and provide quicker interventions. Schools should develop a healthy canteen policy and involve students in promoting healthy food choices. Providing healthy food in the school canteen, with an increased selection of nutritious foods and a reduction of foods high in sugar and saturated fats, is essential.